2015
DOI: 10.4187/respcare.03598
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Resistance Training in Subjects With COPD: A Systematic Review and Meta-Analysis

Abstract: BACKGROUND: The goal of this study was to evaluate the effects of resistance training on subjects with COPD. METHODS: We performed a systematic search in MEDLINE, PubMed, Embase, CINAHL, Elsevier ScienceDirect, EBM Reviews, Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov and also of leading respiratory journals for randomized controlled trials on COPD treatment for > 4 weeks with resistance training compared with non-exercise control or with combined resistance and endurance training com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 53 publications
(87 reference statements)
7
57
0
5
Order By: Relevance
“…Both continuous and interval endurance training have been reported to be effective to improve dyspnea, exercise capacity, and quality of life in patients with COPD . In addition, the combination of endurance and resistance training has been shown to provide greater adaptations in muscle strength and quality of life compared with endurance training alone . Power training has been proven to achieve greater functional benefits than traditional resistance training in older people, and it might be especially beneficial to patients with COPD because of the lower cardiovascular loading and higher muscle oxygenation levels that are experienced during exercise compared with traditional strength training.…”
Section: Introductionmentioning
confidence: 99%
“…Both continuous and interval endurance training have been reported to be effective to improve dyspnea, exercise capacity, and quality of life in patients with COPD . In addition, the combination of endurance and resistance training has been shown to provide greater adaptations in muscle strength and quality of life compared with endurance training alone . Power training has been proven to achieve greater functional benefits than traditional resistance training in older people, and it might be especially beneficial to patients with COPD because of the lower cardiovascular loading and higher muscle oxygenation levels that are experienced during exercise compared with traditional strength training.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, PR (including home‐based PR) may consist of different types of training and support, as well as various protocols (GOLD Science Committee Members ; Reardon, Casaburi, Morgan, Nici, & Rochester, ; Takigawa et al., ). The variations include endurance training (Aquino et al., ), resistance training (RT) (da Silva & Dourado, ), balance training (Beauchamp et al., ) and tai‐chi (Ng et al., ) performed individually or in combination (Liao et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis by Iepsen and colleagues examined studies comparing the effects of combining strength training with endurance training against endurance training alone and concluded that both programs showed similar improvements in physical function and health related quality of life (14). In contrast, a meta-analysis by Liao et al concluded that a combined strength and endurance training program may provide greater improvements in health related quality of life (15). …”
Section: Introductionmentioning
confidence: 99%